JAK1/2 Inhibitor Baricitinib Improves Skin Fibrosis and Digital Ulcers in Systemic Sclerosis - Hou, Zhanying; Su, Xuehan; Han, Guangming; Xue, Ruzeng; Chen, Yangxia; Chen, Ye; Wang, Huan; Yang, Bin; Liang, Yunsheng; Ji, Suyun (Frontiers in Medicine, 2022)
Background: Diffuse cutaneous systemic sclerosis (SSc) is a rare disabling connective tissue disease with few treatment options. Previous experiment has shown that JAK2 inhibitor can significantly improve skin fibrosis in bleomycin (BLM)-induced murine model, including reducing dermal thickening and collagen accumulation. We aimed to describe the efficacy especially focus on skin fibrosis and microvascular manifestations with oral JAK1/2 inhibitor baricitinib in SSc patients. Methods: We described the different effects of oral selective JAK1, JAK2 or JAK3 inhibitor treatment in a BLM-induced skin fibrosis mouse model. Furthermore, 10 adult patients with dcSSc were treated with baricitinib. We assessed the changes in modified rodman skin score (mRSS) and digital ulcer net burden in week 12 and 24 from baseline. We also compared the absolute changes in scores on the Scleroderma Health Assessment Questionnaire (SHAQ), and total score on the St. George’s Respiratory Questionnaire (SGRQ) over a 24-week period. Results: In the experimental mouse model of skin fibrosis, both JAK1 and JAK2 inhibitor ameliorated skin fibrosis and JAK2 inhibitor had the most obvious effect. Treatment with JAK2 inhibitor also blunted the capillary rarefaction. And we demonstrated that skin fibrosis and digital ulcers were significantly relieved in 10 SSc patients treated with baricitinib. The mRSS significantly improved in week 12 from baseline, with a mean change in mRSS of -8.3 (95% CI, -12.03 to -4.574; p=0.0007), and greater in week 24 [-11.67 (95% CI, -16.84 to -6.496; p=0.0008]. Among the 4 patients with digital ulcers, 3 cases completely healed at week 24, the number of ulcers in another one patient was significantly reduced and there was no patient with new ulcers. Only one adverse event (AE) of herpes zoster was observed. Conclusions: Our results indicate that selective JAK1 and JAK2 inhibitor alleviate skin fibrosis and oral JAK1/2 inhibitor baricitinib is a potentially effective treatment for dcSSc patients of skin fibrosis and digital ulcers. Baricitinib was well tolerated by the majority of patients in this study. Additional large clinical trials are needed to corroborate our pilot findings.